Exhaust gas purification catalyst

The use of small rare earth particles supported on a heat-resistant alumina carrier with a noble metal catalyst in a two-layer structure addresses the challenge of maintaining high adsorption performance for NOx and CO across temperature variations, enhancing exhaust gas purification efficiency.

JP7621326B2Active Publication Date: 2025-01-24CATALER CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022501648
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-21
Filing Date
2020-12-07
Publication Date
2025-01-24
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

Existing exhaust gas purification catalysts face challenges in maintaining high NOx and CO adsorption performance at low temperatures and high temperatures due to the coarsening of rare earth particles, which are prone to sintering, and the insufficient performance of chemical purification by precious metal catalysts in low-temperature environments.

Method used

The catalyst employs rare earth particles with an average particle diameter of 10 nm or less supported on a highly heat-resistant alumina carrier, combined with a noble metal catalyst to enhance adsorption and purification performance, and includes a two-layer structure to optimize exhaust gas treatment.

Benefits of technology

The catalyst achieves high NOx and CO purification performance in low-temperature environments and maintains stability at high temperatures, reducing emissions and improving catalyst warm-up performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621326000003
    Figure 0007621326000003
  • Figure 0007621326000004
    Figure 0007621326000004
  • Figure 0007621326000005
    Figure 0007621326000005
Patent Text Reader

Abstract

According to the technique disclosed herein, an exhaust gas purification catalyst exhibiting high exhaust gas purification performance can be provided using a novel material containing a rare earth. The exhaust gas purification catalyst disclosed herein is provided with a base material and a catalyst layer formed on a surface of the base material. The catalyst layer in the exhaust gas purification catalyst comprises rare-earth-supported alumina 50 in which primary particles of rare earth particles 40 each containing at least one rare earth element are supported on the surface of an alumina support 30 containing alumina, wherein the average particle diameter D50 of the rare earth particles 40 in the rare-earth-supported alumina 50 is 10 nm or less as observed with a TEM. It is possible to provide an exhaust gas purification catalyst having high NOx adsorption performance and high CO adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for exhaust gas purification. More specifically, the present invention relates to a catalyst for exhaust gas purification that is disposed in an exhaust passage of an internal combustion engine and purifies exhaust gas emitted from the internal combustion engine. This international application claims priority based on Japanese Patent Application No. 2020-27925 filed on February 21, 2020, the entire contents of which are incorporated herein by reference. [Background technology]

[0002] Exhaust gas discharged from an internal combustion engine such as an automobile engine contains harmful components such as carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx). In order to efficiently purify these harmful components, an exhaust gas purification catalyst is arranged in the exhaust passage of the internal combustion engine. In general, this exhaust gas purification catalyst comprises a substrate and a catalyst layer formed on the surface of the substrate. When exhaust gas comes into contact with the catalyst layer of this exhaust gas purification catalyst, harmful components such as CO, HC, and NOx are rendered harmless by chemical reactions such as oxidation and reduction. In addition, the catalyst layer also has a physical purification effect of adsorbing and collecting harmful components in the exhaust gas.

[0003] In the field of exhaust gas purification catalysts, materials containing rare earth elements (rare earth-containing materials) are added to the catalyst layer for various purposes. For example, in Patent Document 1, a Ce-containing composite oxide, which is an OSC material having oxygen storage capacity (OSC), is added to the catalyst layer. In the exhaust gas purification catalyst disclosed in this document, a Ce-containing composite oxide powder composed of secondary particles (secondary particles with a cumulative distribution 50 mass% particle size of 150 nm to 210 nm) formed by agglomeration of a large number of primary particles with an average particle size of 5 nm to 10 nm is supported on the surface of activated alumina powder.

[0004] Another example is a technology that uses a rare earth-containing material as a NOx adsorbent. For example, in the exhaust gas purification catalyst described in Patent Document 2, a cerium-based material and a lanthanum-based material are added to the catalyst layer. The cerium-based material functions as a NOx adsorbent in a low-temperature environment (150°C to 350°C) under a lean atmosphere, while the lanthanum-based material functions as a NOx adsorbent in a high-temperature environment (350°C to 450°C) under a lean atmosphere. In this way, high NOx purification performance can be achieved by adding compounds of two types of rare earth elements as NOx adsorbents with different optimum temperatures. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 2011-36834 [Patent Document 2] Japanese Patent Application Publication No. 2009-221913 Summary of the Invention [Problem to be solved by the invention]

[0006] However, regulations on harmful components in exhaust gases are becoming stricter year by year, and in response to these tightening regulations, there is also a growing demand for improved performance of exhaust gas purification catalysts. The present inventors conducted various experiments and studies to meet such demands, and as a result, discovered a rare earth-containing material that exhibits effects different from those of conventional materials. The present invention was made based on this discovery, and aims to provide an exhaust gas purification catalyst that uses a novel rare earth-containing material and exhibits high exhaust gas purification performance. [Means for solving the problem]

[0007] As described above, the present inventors have conducted various experiments and studies, and as a result, have discovered a rare earth-containing material that exhibits effects different from those of the past. Specifically, the present inventors have discovered that when particles containing rare earth elements (rare earth particles) are highly dispersed with very small particle diameters, not only does the material exhibit a higher NOx adsorption performance than conventional NOx adsorbents, but also exhibits adsorption performance for CO. When the CO adsorption performance of the rare earth particles is favorably exhibited, it is possible to significantly reduce CO emissions in low-temperature environments (typically immediately after the operation of an internal combustion engine) where chemical purification by a precious metal catalyst does not function sufficiently. In addition, the CO adsorbed by the rare earth particles generates heat when oxidized, which can also contribute to improving the catalyst warm-up performance.

[0008] However, rare earth particles with a small particle size have low heat resistance and are prone to coarsening due to sintering. For this reason, it is difficult to maintain a high level of NOx and CO adsorption performance in exhaust gas purification catalysts, which are heated to 600°C or higher during use. For this reason, the inventors of the present invention conducted further studies and came up with the idea of ​​supporting rare earth particles in the form of small primary particles on an alumina carrier with excellent heat resistance, thereby completing the present invention.

[0009] The catalyst for purifying exhaust gas disclosed herein has been made based on the above findings. This catalyst for purifying exhaust gas is disposed in an exhaust passage of an internal combustion engine and purifies exhaust gas discharged from the internal combustion engine, and includes a substrate and a catalyst layer formed on the surface of the substrate. The catalyst layer of the catalyst for purifying exhaust gas disclosed herein contains rare-earth-supported alumina in which primary particles of rare-earth particles containing at least one rare-earth element are supported on the surface of an alumina carrier containing alumina, and the average particle diameter D of the rare-earth particles in the rare-earth-supported alumina based on TEM observation is 1.0 μm. 50 is less than 10 nm.

[0010] In the exhaust gas purification catalyst disclosed herein, D 50The primary particles of minute rare earth particles with an average particle size of 10 nm or less are supported on an alumina carrier. This allows the rare earth particles to function as active sites that exhibit suitable adsorption performance for NOx and CO. Therefore, the technology disclosed herein can provide an exhaust gas purification catalyst that has high NOx and CO purification performance in a low-temperature environment and excellent catalyst warm-up performance. In this way, the technology disclosed herein can provide an exhaust gas purification catalyst that uses a novel rare earth-containing material and exhibits high exhaust gas purification performance.

[0011] In one embodiment of the exhaust gas purification catalyst disclosed herein, the catalyst layer further contains a precious metal catalyst, which oxidizes CO adsorbed on the rare earth particles and reduces and purifies NOx, thereby achieving even higher purification performance against harmful components in exhaust gas.

[0012] In one embodiment of the exhaust gas purification catalyst disclosed herein, the oxide-equivalent weight of the rare earth particles is 5 wt% to 20 wt% when the oxide-equivalent weight of the alumina support is 100 wt%. This allows fine primary particles of rare earth particles to be supported on the surface of the alumina support in a highly dispersed state, suppressing the coarsening of rare earth particles due to sintering and enabling stable adsorption performance for NOx and CO.

[0013] In one embodiment of the exhaust gas purification catalyst disclosed herein, the alumina support has a specific surface area of ​​50 m2 or less after a durability test at 1000° C. for 10 hours. 2 / g or more. By using a highly heat-resistant alumina support that can maintain a large specific surface area even in high-temperature environments, the coarsening of rare earth particles due to sintering can be more effectively suppressed, allowing the adsorption performance for NOx and CO to be more stable.

[0014] In one embodiment of the exhaust gas purification catalyst disclosed herein, the rare earth particles contain at least one rare earth element selected from the group consisting of Y, La, Ce, Pr, and Nd. The rare earth particles containing these rare earth elements can exhibit favorable adsorption performance for NOx and CO by being dispersed in the state of fine primary particles. Among the rare earth elements described above, Ce is particularly preferred. Typically, the rare earth particles preferably have an oxide-equivalent weight of elements other than Ce of 80 wt% or less when the total amount of the rare earth elements in oxide equivalent is taken as 100 wt%. Such rare earth particles containing Ce as a main element can exhibit particularly favorable adsorption performance for NOx and CO.

[0015] In one embodiment of the exhaust gas purification catalyst disclosed herein, the catalyst layer contains La as the main element of the rare earth particles, and Pd as the precious metal catalyst. The rare earth particles containing La as the main element have the above-mentioned adsorption performance for NOx and CO, as well as the function of improving the reduction action of the precious metal catalyst (Pd). Therefore, according to this embodiment, NH 3 It is possible to suppress emissions. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of an exhaust system of an internal combustion engine in which an exhaust gas purification catalyst is arranged. [Diagram 2] FIG. 2 is a perspective view that typically shows the exhaust gas purifying catalyst according to the first embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing a cross section along the cylinder axis direction of the exhaust gas purifying catalyst according to the first embodiment. [Figure 4] FIG. 4 is a diagram illustrating the rare earth-supported alumina contained in the catalyst layer in one embodiment. [Diagram 5] FIG. 5 is a schematic diagram showing a cross section along the cylinder axis direction of the exhaust gas purifying catalyst according to the second embodiment. [Figure 6]FIG. 6 is a TEM photograph (magnification: 1,200,000 times) of Sample 1 in the test example. [Figure 7] FIG. 7 is a TEM photograph (magnification: 1,200,000 times) of Sample 2 in the test example. [Figure 8] FIG. 8 is a TEM photograph (magnification: 1,200,000 times) of Sample 3 in the test example. [Figure 9] FIG. 9 shows the results of EPMA analysis of Sample 1 in the test example (magnification: 300 times). [Figure 10] FIG. 10 shows the results of EPMA analysis of Sample 2 in the test example (magnification: 300 times). [Figure 11] FIG. 11 shows the results of EPMA analysis of Sample 3 in the test example (magnification: 300 times). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention (e.g., detailed structure of the substrate, etc.) can be understood as design matters of a person skilled in the art based on the prior art in the field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the field.

[0018] <Location of exhaust gas purification catalyst> Fig. 1 is a diagram showing a schematic diagram of an exhaust system of an internal combustion engine in which an exhaust gas purification catalyst is arranged. In each diagram in this specification, arrow A indicates the flow of exhaust gas. For convenience of explanation, in this specification, the side to which exhaust gas is supplied is referred to as the "upstream side (of the flow of exhaust gas)" and the side to which exhaust gas is discharged is referred to as the "downstream side (of the flow of exhaust gas)".

[0019] As shown in FIG. 1, the exhaust gas purification catalyst 1 is disposed in an exhaust passage 3 of an internal combustion engine (engine) 2. The internal combustion engine 2 has a mechanism for burning a mixture containing oxygen and fuel gas, and converting the combustion energy into mechanical energy. As an example, the internal combustion engine 2 is mainly constituted by a gasoline engine. Note that the internal combustion engine 2 may be an engine other than a gasoline engine (e.g., a diesel engine, etc.). The exhaust passage 3 is a gas flow path constituted by an exhaust manifold, an exhaust pipe, etc. The exhaust gas purification catalyst 1 is disposed in the exhaust passage 3 (typically an exhaust pipe). Exhaust gas generated in the internal combustion engine 2 is purified by the exhaust gas purification catalyst 1 and then discharged to the outside.

[0020] Hereinafter, the catalyst for purifying exhaust gas disclosed herein will be described with reference to the first to third embodiments. The catalyst for purifying exhaust gas disclosed herein includes the catalyst for purifying exhaust gas according to each embodiment modified or changed within the scope of design matters of a person skilled in the art. In other words, the catalyst for purifying exhaust gas disclosed herein is not limited to the first to third embodiments.

[0021] <First embodiment> Fig. 2 is a perspective view showing the exhaust gas purifying catalyst according to the first embodiment. Fig. 3 is a view showing a cross section along the cylinder axis direction of the exhaust gas purifying catalyst according to the first embodiment. As shown in Figs. 2 and 3, the exhaust gas purifying catalyst 1 according to this embodiment includes a substrate 10 and a catalyst layer 20 formed on the surface of the substrate 10.

[0022] (1) Base material As shown in FIG. 2, the substrate 10 in this embodiment is a cylindrical substrate having a honeycomb structure. That is, the substrate 10 includes cells 12, which are gas flow paths through which exhaust gas passes, and partition walls 14 that separate adjacent cells 12. The substrate 10 in this embodiment is a so-called straight-flow type substrate. Specifically, as shown in FIG. 3, the cells 12 of the substrate 10 extend along the cylindrical axis direction (exhaust gas flow direction A) of the substrate 10, and both ends of the cells 12 are open. In addition, in the exhaust gas purification catalyst disclosed herein, the structure of the substrate is not particularly limited. For example, a so-called wall-through type substrate having an inlet cell sealed on the downstream side and an outlet cell sealed on the upstream side, in which the inlet cell and the outlet cell are separated by a porous partition wall, can be used. In addition, as a substrate other than a honeycomb shape, a substrate having a foam shape, a pellet shape, or the like can be used. Furthermore, the outer shape of the substrate is not limited to a cylindrical shape, and an elliptical cylinder shape, a polygonal cylinder shape, or the like can be adopted.

[0023] For the substrate 10, various materials conventionally used for this type of application can be used. For example, ceramics having high heat resistance can be used as the material for the substrate 10. As a specific example, the substrate 10 can be made of aluminum oxide (Al 2 O 3 ), cerium oxide (CeO 2 ), titanium dioxide (TiO 2 ), zirconium oxide (ZrO 2 ), silicon oxide (SiO 2 ), Aluminum titanate (Al 2 TiO 5 )) can be used. Other materials include cordierite (2MgO 2Al 2 O 3 5SiO 2 Examples of the ceramic material include composite oxide ceramics such as tantalum oxide (AlO 2 ) and carbide ceramics such as silicon carbide (SiC). Alternatively, alloys such as stainless steel can be used as materials other than ceramics.

[0024] (2)Catalyst layer The catalyst layer 20 is formed on the surface of the substrate 10. Specifically, as shown in FIG. 3, the catalyst layer 20 is formed on the surface of the partition wall 14 that separates the cells 12 inside the substrate 10. The catalyst layer 20 is a porous layer containing a precious metal catalyst. When the exhaust gas comes into contact with the precious metal catalyst in the catalyst layer 20, harmful components (CO, HC, NOx) in the exhaust gas are chemically purified. An example of the precious metal catalyst is a three-way catalyst that oxidizes CO and HC and reduces NOx. Such a three-way catalyst can efficiently purify harmful components in the exhaust gas. An example of the three-way catalyst is a particle that mainly contains platinum group elements such as platinum (Pt), palladium (Pd), rhodium (Rh), ruthenium (Ru), osmium (Os), and iridium (Ir). Among these platinum group elements, Pt, Pd, and Rh can exhibit particularly excellent purification performance against harmful components.

[0025] The precious metal catalyst in the catalyst layer 20 is preferably supported on the surface of the rare earth-supported alumina described later (typically, on the surface of both the alumina carrier and the rare earth particles). This allows the NOx and CO adsorbed on the rare earth particles to be suitably reduced (or oxidized). From the viewpoint of achieving even more suitable purification performance, the content of the precious metal catalyst per 1 L of the capacity of the substrate 11 is preferably 0.1 g / L or more, more preferably 0.5 g / L or more, and particularly preferably 1 g / L or more. On the other hand, from the viewpoint of material cost, the content of the precious metal catalyst is preferably 10 g / L or less, more preferably 8 g / L or less, and particularly preferably 7 g / L or less.

[0026] The catalyst layer 20 in this embodiment contains rare earth-supported alumina. Fig. 4 is a schematic diagram showing the rare earth-supported alumina contained in the catalyst layer in this embodiment. As shown in Fig. 4, the rare earth-supported alumina 50 in this embodiment contains an alumina carrier 30 and rare earth particles 40. Each material constituting the rare earth-supported alumina 50 will be described below.

[0027] (a) Alumina support The alumina carrier 30 is made of alumina (Al2 O 3 In the rare earth-supported alumina 50, the alumina carrier 30 supports the rare earth particles 40 and has a function of preventing the rare earth particles 40 from becoming coarse due to sintering. The alumina carrier 30 may contain any component other than alumina (e.g., lanthanum oxide (La 2 O 3 ), barium oxide (BaO), silicon dioxide (SiO 2 ), titanium dioxide (TiO 2 ) may be included. When the content of alumina is taken as 100 wt%, the content of components other than alumina is preferably 1 wt% to 10 wt%, more preferably 1 wt% to 8 wt%, even more preferably 1 wt% to 5 wt%, and particularly preferably 1 wt% to 4 wt%. This ensures sufficient heat resistance of the alumina carrier 30 and can suitably prevent the rare earth particles 40 from becoming coarse due to sintering. The alumina carrier 30 may be composed of only alumina.

[0028] In addition, the average particle diameter D of the alumina carrier 30 50 is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and particularly preferably 15 μm or more. This ensures sufficient heat resistance of the alumina carrier 30. On the other hand, the average particle diameter D 50 As the specific surface area decreases, the dispersibility of the rare earth particles 40 described below tends to improve. From this viewpoint, the average particle size of the alumina carrier 30 is preferably 100 μm or less, more preferably 70 μm or less, further preferably 50 μm or less, and particularly preferably 30 μm or less.

[0029] In this specification, the "average particle size D 50 " refers to multiple (e.g. 20) particles observed in multiple fields of view (e.g. 4 fields of view) of TEM observation. primary particleThe mean particle diameter D is the arithmetic mean of the equivalent circle diameters of particles. Specifically, the measurement sample is prepared by dispersing the measurement object in a solvent (e.g., a mixed solvent of water and ethanol), dropping it onto a Cu mesh grid, and then drying it. The measurement sample is then observed under a transmission electron microscope (TEM) to measure the long and short diameters of particles observed in a specific range (e.g., 200 nm x 200 nm) of visual field, and the median value is measured as the equivalent circle diameter. The mean particle diameter D is then calculated by calculating the average equivalent circle diameter of the 40 measured particles. 50 " can be requested.

[0030] As described above, when the specific surface area of ​​the alumina carrier 30 is increased, the dispersibility of the rare earth particles 40 is improved, and the adsorption performance for NOx and CO is improved. For this reason, the specific surface area of ​​the alumina carrier 30 is set to 40 m 2 / g or more is preferable, and 50m 2 / g or more is more preferable, and 55m 2 / g or more is more preferable, and 60m 2 The upper limit of the specific surface area of ​​the alumina carrier 30 is not particularly limited, and is preferably 200 m 2 / g or less, and 2 / g or less, and 2 / g or less, and 2 / g or less. During operation of the internal combustion engine 2 (see FIG. 1), the exhaust gas purification catalyst 1 is exposed to a high-temperature environment of 600°C or higher. For this reason, it is preferable that the alumina carrier 30 has excellent heat resistance that allows it to maintain a large specific surface area even in a high-temperature environment. Specifically, the alumina carrier 30 has a specific surface area of ​​45 m2 or less after a durability test at 1000°C for 10 hours. 2 / g or more, and 2 / g or more is more preferable, and 55m 2 More preferably, it is 60m / g or more. 2 / g or more is particularly preferable. This makes it possible to suitably suppress coarsening of the rare earth particles 40 due to sintering, and therefore allows the adsorption performance for NOx and CO to be exhibited more stably.

[0031] (b) Rare earth particles The rare earth particles 40 are particles containing at least one rare earth element. The rare earth particles 40 are fine primary particles (typically having an average particle diameter D 50 The rare earth particles 40 are supported on the surface of the alumina carrier 30 in a state of fine primary particles (primary particles of 10 nm or less). This allows the rare earth particles 40 to be highly dispersed inside the catalyst layer 20 in the state of fine primary particles. According to experiments and studies by the present inventors, when the fine rare earth particles 40 are highly dispersed inside the catalyst layer 20 without forming aggregated particles (secondary particles), the rare earth particles 40 function as active sites for adsorbing NOx and CO, and therefore high NOx adsorption performance and CO adsorption performance can be exhibited. Therefore, the exhaust gas purification catalyst 1 according to this embodiment can remove NOx and CO from exhaust gas and reduce the emission of these harmful components even in a low-temperature environment where chemical purification by a precious metal catalyst does not function sufficiently. Furthermore, the CO adsorbed on the rare earth particles 40 generates heat when oxidized, which can also contribute to improving the catalyst warm-up performance.

[0032] It is not necessary that all the rare earth particles 40 supported on the surface of the alumina carrier 30 are primary particles, and they may partially contain secondary particles. Specifically, when 40% or more (preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more) of the rare earth particles 40 observed by TEM are primary particles, suitable NOx adsorption performance and CO adsorption performance can be exhibited. In addition, the upper limit of the ratio of the primary particles is not particularly limited, and may be 100% (all primary particles) or 80% or less. The above-mentioned "ratio of primary particles of rare earth particles" can be measured by TEM observation. Specifically, in the TEM observation of the measurement sample prepared for the above-mentioned average particle diameter D50, the number of primary particles and secondary particles of rare earth particles confirmed in a specific range (for example, 200 nm x 200 nm) of the visual field is counted. Then, by calculating the ratio of the number of primary particles to the total number of particles (the sum of the number of primary particles and the number of secondary particles) in multiple fields of view (for example, four fields of view), the "ratio of primary particles in rare earth particles" can be obtained.

[0033] As described above, the average particle diameter D of the primary particles of the rare earth particles 40 in this embodiment 50 The average particle diameter D of the primary particles of the rare earth particles 40 is 10 nm or less. By dispersing such fine rare earth particles 40, it is possible to exhibit a suitable adsorption performance for NOx and CO. From the viewpoint of further improving the adsorption performance for NOx and CO, the average particle diameter D of the primary particles of the rare earth particles 40 is set to 10 nm or less. 50 is preferably 9 nm or less, more preferably 8 nm or less, further preferably 7 nm or less, and particularly preferably 6 nm or less. 50 The lower limit of the average particle diameter D of the primary particles of the rare earth particles 40 is not particularly limited, and may be 0.01 nm or more, or may be 0.05 nm or more. 50 As the average particle diameter D of the primary particles of the rare earth particles 40 becomes smaller, the cohesive force between the primary particles becomes stronger, and therefore the secondary particles are more likely to be formed. 50 is preferably 0.1 nm or more, more preferably 0.5 nm or more, further preferably 1 nm or more, and particularly preferably 3 nm or more.

[0034] Furthermore, the rare earth particles 40 preferably have a maximum primary particle diameter of 30 nm or less (more preferably 25 nm or less, even more preferably 23 nm or less, and particularly preferably 20 nm or less). This allows most of the rare earth particles 40 supported on the surface of the alumina carrier 30 to function as active sites for adsorbing NOx and CO. The lower limit of the maximum primary particle diameter is not particularly limited, and may be 1 nm or more, 5 nm or more, 10 nm or more, or 15 nm or more. Note that the "maximum particle diameter of rare earth particles" in this specification refers to the above-mentioned average particle diameter D 50 The circle equivalent diameter refers to the largest circle equivalent diameter among the primary particle diameters of the multiple rare earth particles measured in the calculation of the circle equivalent diameter.

[0035] In addition, examples of rare earth elements contained in the rare earth particles 40 in this embodiment include yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), and neodymium (Nd). The rare earth particles 40 containing at least one of these rare earth elements exhibit suitable adsorption performance for NOx and CO by being highly dispersed in the state of fine primary particles. The rare earth particles 40 may also contain elements other than rare earth elements. Examples of such elements other than rare earth elements include transition metal elements such as zirconium (Zr), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), niobium (Nb), and molybdenum (Mo).

[0036] Among the rare earth elements described above, Ce can exhibit a particularly high level of adsorption performance for NOx and CO. For this reason, the rare earth particles 40 are preferably particles containing Ce as a main element. Typically, when the main element of the rare earth particles 40 is Ce, the oxide-equivalent weight of elements other than Ce relative to the total oxide-equivalent amount of rare earth elements 100 wt% is preferably 80 wt% or less, more preferably 60 wt% or less, even more preferably 40 wt% or less, and particularly preferably 20 wt% or less. This allows the adsorption performance of Ce to be more suitably exhibited. On the other hand, the lower limit of the oxide-equivalent weight of elements other than Ce is not particularly limited. That is, the rare earth particles 40 may be composed of only Ce. Here, the "elements other than Ce" also include rare earth elements other than Ce (Y, La, Pr, Nd, etc.).

[0037] As will be described in detail in the third embodiment below, among the rare earth elements, La has a function of enhancing the chemical purification performance of the precious metal catalyst (Pd). Therefore, among the rare earth elements described above, Ce and La are suitable as main elements constituting the rare earth particles 40.

[0038] (c) Other additives In addition, materials other than the precious metal catalyst and the precious metal-supported alumina may be added to the catalyst layer 20. For example, when a three-way catalyst is used as the precious metal catalyst, it is preferable that an OSC material is added to the catalyst layer 20. Such an OSC material is a metal oxide (e.g., ceria-zirconia composite oxide) that has the function of absorbing and releasing oxygen. By adding such an OSC material to the catalyst layer 20, the air-fuel ratio of the exhaust gas can be maintained close to the stoichiometric (theoretical air-fuel ratio), and the chemical purification action of the precious metal catalyst can be stably exerted. In addition, other examples of additives contained in the catalyst layer 20 include a stabilizer and a binder.

[0039] The first embodiment of the exhaust gas purifying catalyst disclosed herein has been described above. However, the exhaust gas purifying catalyst disclosed herein is not limited to the embodiment, and includes various modifications and variations.

[0040] <Second embodiment> Next, a second embodiment of the exhaust gas purifying catalyst disclosed herein will be described. Fig. 5 is an enlarged view of a cross section along the cylinder axis direction of the exhaust gas purifying catalyst according to the second embodiment.

[0041] As shown in FIG. 5, in the exhaust gas purification catalyst 1 according to the first embodiment, a catalyst layer 20 consisting of a single layer is formed on the surface of the partition wall 14 of the substrate 10. However, the catalyst layer is not limited to such a form, and may have a multi-layer structure of two or more layers. For example, as shown in FIG. 5, in the exhaust gas purification catalyst 1 according to the second embodiment, a catalyst layer 20 having a two-layer structure consisting of a lower layer 22 and an upper layer 24 is formed. In this case, the rare earth-supported alumina may be added to either the lower layer 22 or the upper layer 24, or may be added to both layers. When the rare earth-supported alumina is added to either the lower layer 22 or the upper layer 24, it is preferable that the rare earth-supported alumina is added to the lower layer 22. Immediately after the internal combustion engine is started, the flow rate of the exhaust gas is low, so that the exhaust gas is easily supplied to the lower layer side of the catalyst layer 20. Therefore, by adding rare earth-loaded alumina capable of removing NOx and CO by adsorption to the lower layer 22, it is possible to suitably suppress the emission of NOx and CO in a low-temperature environment immediately after the internal combustion engine is started.

[0042] In addition, when forming a catalyst layer 20 having a two-layer structure as shown in FIG. 5, the type and content of the precious metal catalyst can be made different between the lower layer 22 and the upper layer 24. In this case, it is preferable to adjust the type and content of the precious metal catalyst in each layer, taking into consideration the flow rate of the exhaust gas and the content of harmful components. According to the study by the present inventors, rare earth-supported alumina (Ce-supported alumina) having rare earth particles whose main element is Ce exhibits excellent adsorption performance for NOx and CO, but may inhibit the catalytic activity of rhodium (Rh). For this reason, when using Ce-supported alumina, it is preferable to add Ce-supported alumina to a catalyst layer to which Rh is not added. As an example, when the precious metal catalyst of the upper layer 22 is Rh and the precious metal catalyst of the lower layer 24 is Pd, it is preferable to add Ce-supported alumina to the lower layer 24. In addition, either the lower layer 22 or the upper layer 24 constituting the catalyst layer 20 may be a catalyst-less layer that does not contain a precious metal catalyst. In this case, by adding rare earth-supported alumina to the catalyst-less layer, the catalyst-less layer can function as a NOx·CO adsorption layer.

[0043] <Third embodiment> As described above, according to the study by the present inventors, it has been confirmed that rare earth-supported alumina (La-supported alumina) having rare earth particles whose main element is La has a function of enhancing the chemical purification performance of a precious metal catalyst. In the third embodiment, a catalyst for purifying exhaust gas in which such La-supported alumina is added to a catalyst layer will be described.

[0044] As described above, in the exhaust gas purification catalyst disclosed herein, rare earth particles containing rare earth elements (Y, La, Ce, Pr, Nd, etc.) are supported on an alumina carrier in the form of fine primary particles. However, among these rare earth particles, rare earth particles containing La as a main element have a function of improving the chemical purification performance of Pd when coexisting with palladium (Pd) in a catalyst layer. Specifically, in a typical exhaust gas purification catalyst, the electronic state of Pd present in the catalyst layer is zero to two valences. However, in a catalyst layer in which fine La particles are highly dispersed, the electronic state of Pd can increase to four valences. Such four valent Pd has a strong reducing effect on NOx, and therefore can purify NOx more suitably. For example, when the reduction of NOx in exhaust gas is incomplete, ammonia (NH 3 However, according to the present embodiment, the incomplete reduction of NOx is suppressed, and NH 3 Emissions can be significantly reduced.

[0045] In addition, the coexistence of La-loaded alumina and Pd resulted in NH 3 The reduction effect is preferably exhibited when the weight of the oxide of other elements is 80 wt% or less when the weight of the oxide of La in the rare earth particles is 100 wt% (i.e., the rare earth particles contain La as the main element). 3 From the viewpoint of more optimally exerting the reduction effect, the weight of the other elements in terms of oxide is suitably 60 wt% or less, preferably 40 wt% or less, more preferably 20 wt% or less, even more preferably 15 wt% or less, and particularly preferably 10 wt% or less, for example, 0 wt% (rare earth particles composed only of La).

[0046] In this embodiment, a precious metal catalyst other than Pd (Rh, Pt, etc.) may be contained in the catalyst layer. 3From the viewpoint of more effectively exerting the reduction effect, a larger Pd content is preferable. For example, when the Pd content in the catalyst layer is 100 wt%, the content of other precious metal catalysts is preferably 80 wt% or less, more preferably 60 wt% or less, further preferably 40 wt% or less, particularly preferably 20 wt% or less, and for example, 0 wt% (only Pd is added as the precious metal catalyst).

[0047] In addition, N.H. 3 The reduction effect can vary depending on the weight ratio of La to the alumina carrier in the La-supported alumina, the Pd content relative to the specific surface area of ​​the alumina carrier, the Pd content relative to the pore volume of the catalyst layer, etc. For example, when the content of the alumina carrier is taken as 100 wt%, the content of the rare earth particles (La) is preferably 1 wt% to 50 wt%, more preferably 2 wt% to 40 wt%, further preferably 3 wt% to 30 wt%, and particularly preferably 4 wt% to 15 wt%. This reduces the amount of NH 3 The reduction effect can be further improved.

[0048] <Method of manufacturing exhaust gas purification catalyst> Next, a method for producing the exhaust gas purifying catalyst according to the present embodiment will be described. This production method includes a step of preparing rare earth-supported alumina and a step of forming a catalyst layer on the surface of a substrate.

[0049] (1) Preparation of rare earth-supported alumina In this process, rare earth-supported alumina is produced by supporting rare earth particles on the surface of the alumina support. In this process, first, a solution in which rare earth elements are sufficiently dissolved (rare earth solution) is prepared. Then, the rare earth solution is attached to the surface of the alumina support, and then dried and fired. In this way, rare earth-supported alumina can be produced in which primary particles of rare earth particles are supported on the surface of the alumina support.

[0050] In order to support rare earth particles having a sufficiently small particle size on the surface of the alumina support in a highly dispersed state, it is preferable to use a spray drying method in this process. Specifically, the alumina support is suspended inside a flow path through which an inert gas flows, and a rare earth solution is sprayed into the flow path. As a result, very fine droplets of the rare earth solution adhere to the surface of the alumina support, and by firing this, the average particle diameter D 50 Primary particles of rare earth particles having a diameter of 10 nm or less can be easily supported on the surface of the alumina carrier. When adopting such a spray drying method, it is preferable to spray the rare earth solution so that the droplet diameter is 800 μm or less (more preferably 600 μm or less, further preferably 500 μm or less, and particularly preferably 400 μm or less). This allows rare earth particles with a small particle diameter to be stably supported on the alumina carrier.

[0051] (2) Formation of the catalyst layer Next, in this step, a catalyst layer containing rare earth-supported alumina is formed on the surface of the substrate. The means for forming the catalyst layer in this step is not particularly limited, and a conventionally known method can be adopted without particular limitation. For example, first, a slurry is prepared by dispersing various materials (precious metal catalyst, OSC material, etc.) containing rare earth-supported alumina in a dispersion medium (water, etc.). Next, the slurry is introduced into the cells of the substrate, and then adhered to the partition wall surface of the substrate using an air blower or the like. Then, drying and firing are performed under predetermined conditions. As a result, a catalyst layer containing rare earth-supported alumina is formed on the surface of the partition wall of the substrate, and a catalyst for exhaust gas purification is produced. Note that, from the viewpoint of reliably preventing the rare earth particles contained in the rare earth-supported alumina from becoming coarse due to sintering, it is preferable to dry and fire the slurry in this step at a temperature condition of 600°C or less.

[0052] The method for producing the exhaust gas purifying catalyst according to the present embodiment has been described above. However, the exhaust gas purifying catalyst disclosed herein has an average particle diameter D 50 It is sufficient that rare earth-supported alumina containing rare earth particles having a size of 10 nm or less is added to the catalyst layer, and there is no limitation on the manufacturing method.

[0053] [Test example] Test examples relating to the present invention will be described below, but it is not intended that the present invention be limited to those shown in the following test examples.

[0054] <First experiment> In this experiment, we investigated the effects of the particle size and dispersibility of rare earth particles in rare earth-loaded alumina on NOx adsorption performance and CO adsorption performance.

[0055] 1. Sample Preparation (1) Sample 1 In this sample, rare earth-supported alumina (Ce-supported alumina) prepared by spray drying was added to the lower layer of an exhaust gas purification catalyst having a two-layered catalyst layer structure consisting of an upper layer and a lower layer.

[0056] Specifically, a rare earth solution (Ce solution) was prepared by dissolving a compound (cerium nitrate hexahydrate) containing a rare earth element (Ce) in a solvent (water). 2 O 3 ) containing 5wt% La 2 O 3 A composite alumina was prepared as an alumina support. Then, a Ce solution was attached to the alumina support using a spray drying method, and then sintering (500°C, 2 hours) was performed to produce Ce-loaded alumina. In this sample, the supply amount of the Ce solution in the spray drying method was adjusted so that 15 wt% of Ce was loaded on 100 wt% of the alumina support.

[0057] Next, palladium nitrate, Ce-loaded alumina, and OSC material (CeO 2 -ZrO 2 Complex oxide) and barium sulfate (BaSO 4 ) and binder (Al 2 O 3A slurry for the lower layer was prepared by mixing a fluorine-based binder and a solvent (water). This slurry for the lower layer was introduced into the cells of the substrate and air-blowing was performed, followed by drying (120°C, 2 hours) and firing (500°C, 2 hours) to form a lower layer of the catalyst layer on the surface of the partition wall of the substrate. The substrate used in this test was a straight-flow substrate made of cordierite with a honeycomb structure having a capacity of 850cc, a partition wall thickness of 2mm, and a cell number of 900 cells. In this sample, the components of the slurry for the lower layer and the amount of the slurry supplied to the substrate were adjusted so that the lower layer after formation contained 2.0g / L of Pd, 50g / L of Ce-supported alumina, 20g / L of OSC material, and 5.0g / L of barium sulfate.

[0058] Next, rhodium nitrate and an alumina support (La 2 O 3 Composite alumina) and OSC material (CeO 2 -ZrO 2 composite oxide) and binder (Al 2 O 3 A slurry for the upper layer was prepared by mixing a fluorine-based binder and a solvent (water). This slurry for the upper layer was introduced into the cells of the substrate and air-blowing was performed, followed by drying (120°C, 2 hours) and firing (500°C, 2 hours) to form an upper layer on the surface of the lower layer. In this way, a catalyst for exhaust gas purification was produced that had a two-layered catalyst layer and contained Ce-loaded alumina in the lower layer. In forming the upper layer, the components of the slurry for the upper layer and the amount of the slurry supplied into the substrate were adjusted so that 0.13 g / L of Rh, 55 g / L of the alumina carrier, and 50 g / L of the OSC material were contained in the upper layer after formation.

[0059] (2) Sample 2 For Sample 2, a catalyst for purifying exhaust gas was prepared by the same procedure as for Sample 1, except that a Ce-loaded alumina was prepared with a smaller amount of Ce loaded than in Sample 1. In this sample, the supply amount of the Ce solution in the spray drying method was adjusted so that 5 wt% of Ce was loaded on 100 wt% of the alumina support.

[0060] (3) Sample 3 For sample 3, an exhaust gas purification catalyst was prepared using the same procedure as for sample 1, except that a Ce-supported alumina prepared using the immersion method was used. In preparing the Ce-supported alumina for this sample, first, the alumina support (La 2 O 3 A Ce-loaded alumina composite was immersed in the solution. The solution was then dried (250°C, 2 hours) and fired (500°C, 2 hours) to obtain Ce-loaded alumina. The resulting powder was then crushed to adjust the particle size.

[0061] 2.Evaluation Test (1) Microscopic observation In the above manufacturing process, a part of the Ce-loaded alumina before being added to the catalyst layer (lower layer) was collected and added to a mixed solvent of ethanol and water. Then, after dispersion was performed using an ultrasonic dispersion device, the dispersion liquid was dropped onto a grid of Cu mesh and dried to prepare a measurement sample. Then, the sample was observed with a transmission electron microscope (manufactured by JEOL, model: JEM-F200) and a TEM photograph was taken. An example of a TEM photograph (magnification: 1200000 times) of Sample 1 is shown in FIG. 6, an example of a TEM photograph of Sample 2 is shown in FIG. 7, and an example of a TEM photograph of Sample 3 is shown in FIG. 8. In these TEM photographs, the white parts indicate Ce particles.

[0062] In the above TEM observation, the circle equivalent diameters of 10 Ce particles were measured in each of the four fields of view, and the "average particle diameter D of Ce particles" was calculated based on the measurement results. 50 The measurement results are shown in Table 1. The maximum particle diameter D Max The results are also shown in Table 1. Furthermore, in this test, the numbers of primary and secondary Ce particles were counted in four fields of view, and the ratio of the number of primary particles to the total number of particles (number of primary particles + number of secondary particles) was calculated to determine the "ratio of primary particles in Ce particles." The measurement results are also shown in Table 1.

[0063] In addition, in this test, EPMA analysis was performed on the measurement samples containing Ce-loaded alumina to examine the distribution of Ce particles loaded on the surface of the alumina carrier. The results of the EPMA analysis of Sample 1 (magnification: 300x) are shown in Figure 9, the results of the EPMA analysis of Sample 2 in Figure 10, and the results of the EPMA analysis of Sample 3 in Figure 11. In these photographs, the white areas indicate Ce particles.

[0064] (2) Adsorption performance evaluation Each sample catalyst for exhaust gas purification was attached to an engine bench, and exhaust gas containing NOx and CO was supplied to evaluate the NOx adsorption performance and CO adsorption performance. 2 Gas (flow rate: 8 L / min) was supplied for 6 minutes, and the catalyst for exhaust gas purification was heated to 200°C. Then, while maintaining the temperature, hydrogen-containing N 2 A reduction treatment was carried out by supplying N gas for 2 minutes. 2 After performing a gas replacement process in which gas was supplied for 1 minute, 2000 ppm of nitric oxide (NO) and 3000 ppm of carbon monoxide (CO) were replaced with N 2 The mixture was mixed into the gas and supplied for 4 minutes. The NO concentration on the upstream side and the NO concentration on the downstream side of the sample were then measured, and the NO adsorption rate was calculated based on the following formula (1) to evaluate the NOx adsorption performance. Similarly, the CO concentration on the upstream side and the CO concentration on the downstream side of the sample were then measured, and the CO adsorption rate was calculated based on the following formula (2) to evaluate the CO adsorption performance. The measurement results are shown in Table 1. NO adsorption rate = (upstream NO concentration - downstream NO concentration) / upstream NO concentration x 100 (1) CO adsorption rate = (upstream CO concentration - downstream CO concentration) / upstream CO concentration x 100 (2)

[0065] [Table 1]

[0066] 3. Evaluation results As shown in Figs. 6 to 11 and Table 1, the Ce-loaded alumina (samples 1 and 2) prepared by the spray drying method had an average particle diameter D 50 In sample 3, a large number of secondary particles formed by aggregation of primary Ce particles were observed, and the average particle diameter D 50 and maximum particle size D Max In both cases, it was larger than samples 1 and 2. Furthermore, when the adsorption performance for NOx and Co was examined, samples 1 and 2 exhibited higher performance than sample 3. From this, it was found that Ce-loaded alumina, in which fine Ce particles with an average particle size of 10 nm or less are highly dispersed and loaded on the surface of an alumina carrier, as in samples 1 and 2, exhibits high purification performance for NOx and CO when added to the catalyst layer of an exhaust gas purification catalyst.

[0067] <Second experiment> In this experiment, the effects of elements (elements other than Ce) contained in rare earth particles (Ce particles) on NOx adsorption performance and CO adsorption performance were investigated.

[0068] 1. Sample Preparation (1) Sample 4 For Sample 4, an exhaust gas purification catalyst was prepared using the same procedure as for Sample 1, except that a Ce-loaded alumina was prepared with a larger amount of Ce loaded than in Sample 1 of the first test. In this sample, the amount of Ce solution supplied in the spray drying method was adjusted so that 20 wt% of Ce was loaded on 100 wt% of the alumina support.

[0069] (2) Sample 5 For Sample 5, an exhaust gas purification catalyst was prepared using the same procedure as for Sample 4, except that Pr was added to the rare earth solution (Ce solution) sprayed in the spray drying method. In this sample, the concentrations of Ce and Pr in the rare earth solution were adjusted so that 4 wt% of Ce was supported and 16 wt% of Pr was supported on 100 wt% of the alumina support, and the supply amount of the rare earth solution in the spray drying method was also adjusted. In Sample 5, the total amount of rare earth particles supported was 20 wt%, and the ratio of elements other than Ce (Pr) to the total amount supported was 80%.

[0070] (3) Sample 6 For Sample 6, an exhaust gas purification catalyst was prepared by the same procedure as for Sample 5, except that the amount of rare earth supported was smaller than that for Sample 5. In this sample, the supply amount of rare earth solution in the spray drying method was adjusted so that 10 wt % of rare earth particles were supported on 100 wt % of the alumina support.

[0071] (4) Sample 7 For sample 7, an exhaust gas purification catalyst was prepared using the same procedure as for sample 5, except that the amount of Pr added to the rare earth solution was reduced. Note that for this sample, the concentrations of Ce and Pr in the rare earth solution were adjusted so that Pr was 10 wt% of the total amount of rare earth particles supported.

[0072] (5) Sample 8 For sample 8, an exhaust gas purification catalyst was prepared using the same procedure as for sample 4, except that Ce and Nd were added to the rare earth solution sprayed in the spray drying method. In this sample, the concentrations of Ce and Nd in the rare earth solution were adjusted so that Nd was 20 wt% of the total supported amount of rare earth particles.

[0073] (6) Sample 9 For sample 9, an exhaust gas purification catalyst was prepared in the same manner as for sample 8, except that the elements added to the rare earth solution were changed to Ce and Y.

[0074] (7) Sample 10 For Sample 10, an exhaust gas purification catalyst was prepared in the same manner as for Sample 8, except that the elements added to the rare earth solution were changed to Ce and Zr.

[0075] (7) Sample 11 In sample 11, when forming the lower layer of the catalyst layer, an alumina carrier (La 2 O 3 An exhaust gas purification catalyst was prepared in the same manner as in Sample 4, except that composite alumina was added.

[0076] (8) Samples 12 to 14 In Samples 12 to 14, exhaust gas purification catalysts were prepared in the same manner as Sample 4, except that La-supported alumina, which is rare earth-supported alumina having rare earth particles whose main element is La, was used instead of Ce-supported alumina. As shown in Table 2, in Samples 12 to 14, the amount of La supported relative to 100 wt% of the alumina support was varied by adjusting the amount of La solution supplied in the spray drying method.

[0077] 2.Evaluation Test The NO adsorption rate and CO adsorption rate of each sample were determined using the same procedure as in the first test described above. The results are shown in Table 2. Table 2 also shows the NO adsorption rate and CO adsorption rate of Samples 1 to 3 measured in the first test.

[0078] [Table 2]

[0079] 3. Evaluation results Although not shown in the figure, TEM observation was performed on each sample, and the average particle diameter D 50 It was confirmed that minute Ce particles of 10 nm or less were supported on the surface of the alumina support in a highly dispersed state.

[0080] Next, as shown in Table 2, from the results of samples 1, 2, and 4, it was found that if the amount of Ce particles supported on the alumina carrier is within the range of 5 to 20 wt%, it can exhibit suitable adsorption performance for NOx and CO. Next, from the results of samples 5 to 9, it was found that when the main element of the rare earth particles is Ce, even if other rare earth elements are added, it can exhibit suitable adsorption performance for NOx and CO. It was also confirmed that the amount of other elements added in this case is preferably 80 wt% or less with respect to the total amount of the rare earth particles. In addition, from the results of sample 10, it was found that even if Zr, a metal element other than rare earth elements, is added, it exhibits suitable adsorption performance for NOx and CO. In addition, as shown in samples 12 to 14, when the main element of the rare earth particles is La, it is possible to construct an exhaust gas purification catalyst with particularly high adsorption performance for NOx, and it was found that when the amount of support is 15 wt%, it exhibits CO adsorption performance equivalent to that of Ce.

[0081] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Industrial Applicability]

[0082] According to the present invention, it is possible to provide an exhaust gas purification catalyst that exhibits high exhaust gas purification performance. Such an exhaust gas purification catalyst has high NOx and CO purification performance in a low-temperature environment and is excellent in catalyst warm-up performance, so that it can suitably purify exhaust gas emitted in a low-temperature environment where chemical purification by a precious metal catalyst does not function sufficiently.

Claims

1. An exhaust gas purifying catalyst that is disposed in an exhaust passage of an internal combustion engine and purifies exhaust gas discharged from the internal combustion engine, The present invention includes a substrate and a catalyst layer formed on a surface of the substrate, the catalyst layer contains rare earth-supported alumina in which primary particles of rare earth particles containing at least one rare earth element are supported on a surface of an alumina carrier containing alumina, The average particle diameter D of the primary particles based on TEM observation of the rare earth particles in the rare earth-supported alumina 50 is 10 nm or less, The exhaust gas purifying catalyst, wherein 60% or more of the rare earth particles confirmed by the TEM observation are primary particles.

2. The exhaust gas purifying catalyst according to claim 1 , wherein the catalyst layer further contains a precious metal catalyst.

3. 3. The exhaust gas purifying catalyst according to claim 1, wherein the weight of the rare earth particles in terms of oxides is 5 wt % or more and 20 wt % or less when the weight of the alumina support in terms of oxides is taken as 100 wt %.

4. The alumina carrier has a specific surface area of ​​50 m after a durability test at 1000° C. for 10 hours. 2 The exhaust gas purifying catalyst according to any one of claims 1 to 3, wherein the Mo content is 1 / g or more.

5. 5. The exhaust gas purifying catalyst according to claim 1, wherein the rare earth particles contain at least one rare earth element selected from the group consisting of Y, La, Ce, Pr, and Nd.

6. The rare earth particles contain Ce, 6. The exhaust gas purifying catalyst according to claim 5, wherein the weight of said Ce in terms of oxides is 20 wt % or more relative to 100 wt % of the total amount of rare earth elements in said rare earth particles in terms of oxides.

7. 7. The exhaust gas purifying catalyst according to claim 6, wherein the rare earth particles contain elements other than Ce in an amount of 80 wt % or less in terms of oxides when the total amount of the rare earth elements in terms of oxides is taken as 100 wt %.

8. The catalyst layer contains La in the rare earth particles and Pd as a precious metal catalyst, 6. The exhaust gas purifying catalyst according to claim 5, wherein the weight of said La in terms of oxides is 20 wt % or more relative to 100 wt % of the total amount of rare earth elements in said rare earth particles in terms of oxides.

Citation Information

Patent Citations

  • Exhaust emission control device

    JP2009221913A

  • Catalyst for cleaning exhaust, and method of producing the same

    JP2011036834A

  • Method for manufacturing single-nanoparticle-supporting compound, single-nanoparticle-supporting compound obtained by the method

    JP2011144083A

  • Exhaust gas purification catalyst

    JP2012187518A

  • Promoter for exhaust gas purification and production process therefor

    JP2013154261A